2022
DOI: 10.1007/s10880-022-09857-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resilience, Alexithymia and Subjectively Perceived Helplessness of Myocardial Infarction on the Risk of Posttraumatic Stress

Abstract: The aim of this study was to investigate the impact of resilience, alexithymia and the subjectively perceived severity (fear of death, pain intensity, helplessness) of myocardial infarction (MI) on posttraumatic symptom severity (PTSS) after MI. Patients were assessed with the Posttraumatic Diagnostic Scale (PDS), Resilience Scale (RS-11) and Toronto Alexithymia Scale (TAS-20). Subjectively perceived severity of MI was measured with three items on a 10-point Likert scale. To test our hypothesis, we applied Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Consistent with existing research, individuals with high-level resilience can cope better with negative emotions [73]. Other studies confirmed that individuals with dysphoria generally have low-level psychological resilience and cannot cope better with negative emotions [74]. This may be because low expressive skills in individuals with dysphoria have limited attention and memory processes, making it difficult to connect with external and sensory experiences and manage and report their feelings.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with existing research, individuals with high-level resilience can cope better with negative emotions [73]. Other studies confirmed that individuals with dysphoria generally have low-level psychological resilience and cannot cope better with negative emotions [74]. This may be because low expressive skills in individuals with dysphoria have limited attention and memory processes, making it difficult to connect with external and sensory experiences and manage and report their feelings.…”
Section: Discussionsupporting
confidence: 68%
“…A complex neural–immuno–cutaneous–endocrine network may act as an independent local stress response system [ 53 , 54 , 55 ]. Alexithymia and subjectively perceived helplessness appear to positively correlate with post-traumatic stress, but the nature and direction of causality is unclear, as is also the case for alexithymia and AD [ 56 ].…”
Section: Mental Health Conditions Associated With Admentioning
confidence: 99%
“…A second group (10%) shows a chronic worsening course. Finally, only 3% can be classified into an acute-recovering trajectory group characterized by initially high PTSD symptoms that steadily decrease over the course of 1 year [ 53 ]. On the other hand, social support [ 54 ], resilience factors (including internal control beliefs, humor, and patience) [ 55 ], as well as repressive coping strategies immediately after the traumatic event have been shown to have a protective effect with regard to the development of CDI-PTSD symptoms [ 56 ].…”
Section: Background and Introductionmentioning
confidence: 99%